Pharmaceutical solids in crystal engineering - Nangia, Ashwini (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: cocrystals; crystal engineering; Supramolecular synthon

Pharmaceutical cocrystals: walking the talk - Bolla, Geetha; Nangia, Ashwini (Chemical Communications, 2016)
Pharmaceutical cocrystals belong to a sub-class of cocrystals wherein one of the components is a drug molecule (or an active pharmaceutical ingredient, API) and the second is a benign food or drug grade additive (generally regarded as safe, GRAS). The two components are hydrogen-bonded in a fixed stoichiometric ratio in the crystal lattice. In the past decade, pharmaceutical cocrystals have demonstrated significant promise in their ability to modify the physicochemical and pharmacokinetic properties of drug substances, such as the solubility and dissolution rate, bioavailability, particle morphology and size, tableting and compaction, melting point, physical form, biochemical and hydration stability, and permeability. In this feature review, we highlight some prominent examples of drug cocrystals which exhibit variable hardness/softness and elasticity/plasticity depending on coformer selection, improvement of solubility and permeability in the same cocrystal, increase of the melting point for solid formulation, enhanced color performance, photostability and hydration stability, and a longer half-life. Cocrystals of flavanoids and polyphenols can make improved pharmaceuticals and also extend to the larger class of nutraceuticals. The application of crystal engineering to assemble ternary cocrystals expands this field to drug-drug cocrystals which may be useful in multi-drug resistance, mitigating side effects of drugs, or attenuating/enhancing drug action synergistically by rational selection. The advent of new techniques for structural characterization beyond the standard X-ray diffraction will provide a better understanding of drug phases which are at the borderline of crystalline-amorphous nature and even newer opportunities in the future.

Polymorphism, isostructurality and physicochemical properties of glibenclamide salts - Suresh, Kuthuru; Khandavilli, U. B. Rao; Gunnam, Anilkumar; Nangia, Ashwini (CrystEngComm, 2017)
Novel salts of glibenclamide (GBA), namely glibenclamide-sodium (GBA-Na), glibenclamide-potassium (GBA-K) and glibenclamide-ammonium (GBA-NH4) were crystallized under different conditions to obtain their polymorphs, and their aqueous solubility and hydration stability studies are reported. The GBA-Na salt is dimorphic (forms I and II)and also exists as hydrate GBA-Na-H2O (form III). The GBA-K salt exists in anhydrous and hydrate forms (GBA-K, forms I and II). Crystal structure analysis of GBA-Na forms I and II showed differences in geometry of the central metal atom and ligand orientation. This kind of polymorphism of sulfonyl urea salts appears to be novel in the Cambridge Structural Database (CSD). The iso-structurality of GBA-Na form I with GBA-NH4 and GBA-K form I salts is discussed. The potassium salts of GBA exhibited higher solubility compared to pure GBA. Specifically GBA-K salt forms I and II showed higher solubility by 77 fold in the water and 33 fold in phosphate buffer (pH 7) compared to the other salts. Dynamic vapor sorption (DVS) showed reversible water sorption without hysteresis for all salts, except for GBA-K form II which transformed to form I after a sorption and desorption cycle as confirmed by PXRD.